2013
DOI: 10.1371/journal.pone.0078597
|View full text |Cite
|
Sign up to set email alerts
|

No Effects of Psychosocial Stress on Intertemporal Choice

Abstract: Intertemporal choices - involving decisions which trade off instant and delayed outcomes - are often made under stress. It remains unknown, however, whether and how stress affects intertemporal choice. We subjected 142 healthy male subjects to a laboratory stress or control protocol, and asked them to make a series of intertemporal choices either directly after stress, or 20 minutes later (resulting in four experimental groups). Based on theory and evidence from behavioral economics and cellular neuroscience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 58 publications
3
54
1
Order By: Relevance
“…However, a reanalysis of the data revealed that increased discount rates could be accounted for by increased random responding likely induced by the distraction of having to perform the memory task simultaneously (Franco-Watkins et al, 2006). Haushofer et al (2013) found that neither subjective stress ratings, nor free cortisol levels assayed from salivary samples, were associated with changes in discount rates.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, a reanalysis of the data revealed that increased discount rates could be accounted for by increased random responding likely induced by the distraction of having to perform the memory task simultaneously (Franco-Watkins et al, 2006). Haushofer et al (2013) found that neither subjective stress ratings, nor free cortisol levels assayed from salivary samples, were associated with changes in discount rates.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, it has been suggested that the capacity for self-control is limited and vulnerable to temporary depletion by excessive loads (Muraven and Baumeister, 2000). Studies investigating the effects of cognitive demand and stress on delay discounting have yielded mixed results (Hinson et al, 2003; Haushofer et al, 2013). Hinson and colleagues (2003) found that maintaining longer strings of digits in memory was associated with greater discounting of delayed rewards.…”
Section: Introductionmentioning
confidence: 99%
“…Although stress hormones impact a number of brain regions related to decision-making [65], the effects of stress on intertemporal choice are inconsistent. One study found that individuals became more impulsive under stress [66], whereas another found that there were no effects [67], and yet another found that these effects depended on individual differences in perceived stress [68]. Therefore, the conditions under which stress influences intertemporal choice remains an open question.…”
Section: Incidental Carryover Effects On Intertemporal Choicementioning
confidence: 99%
“…The SIDI model would predict that stress potentiates these biases. In addition to the several biases mentioned before (e.g., the framing effect and reflection effect), there are many other biases that should be examined to further test the SIDI model, such as social conformity (Huang et al., 2014, Asch, 1955), the decoy bias (Hu and Yu, 2014, Huber et al., 1982), the default bias (Yu et al., 2010), delay discounting (Yu, 2012, Mischel et al., 1989, Haushofer et al., 2013, Haushofer and Fehr, 2014), and availability (Tversky & Kahneman, 1974). For example, it is reasonable to predict that individuals would be more vulnerable to social influence if they rely more on System 1 to make decisions, as the SIDI model posits.…”
Section: A Stress Induced Deliberation-to-intuition (Sidi) Modelmentioning
confidence: 99%